2016
DOI: 10.1016/j.jafrearsci.2016.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Mineral chemistry and petrology of mantle peridotites from the Guleman ophiolite (SE Anatolia, Turkey): Evidence of a forearc setting

Abstract: The mantle section of Guleman ophiolite, southeast (SE) Turkey consists mainly of harzburgites and dunite lenses and large chromitite pods. The average Cr ratio ¼ [100 Â Cr/(Cr þ Al) atomic ratio] of Crspinels in harzburgites and dunites is remarkably high (>63). The forsterite (Fo) content of olivine is between 90.9 and 92.3 in harzburgites and dunites. These features indicate that the harzburgites and dunites resulted from >35% of partial melting of a depleted mantle source. Discriminant geochemical diagrams… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 58 publications
(76 reference statements)
0
3
0
3
Order By: Relevance
“…Birim için içerisinde bulunan kırmızı renkli kireçtaşlarından derlenen fosil içeriklerine göre, Kampaniyen-Maastrihtiyen [22], radyolarya ve planktik foraminifer içeriklerine göre [11,14] ise Senomaniyen-Maastrihtiyen (Geç Kretase) yaşı verilmiştir [15][16][17][18]. Birim için, güneye dalımlı okyanus içi ada yayı [23,24], aktif kıta kenarı [25] kuzeye dalımla gelişen ada yayı [26][27][28][29], ada yayı [30][31][32][33], okyanusal yay ortamları [34,35] ile okyanus içi yay-yay ardı sisteminde [11,12] oluştukları görüşleri kabul edilmiştir [14,36]. YK, Asker Dağı (Elazığ KD) civarında yaygın yastık lav morfolojili yüzlekler sunar [15][16][17].…”
Section: Sonuçlar Ve Tartışmalar (Results and Discussion)unclassified
See 1 more Smart Citation
“…Birim için içerisinde bulunan kırmızı renkli kireçtaşlarından derlenen fosil içeriklerine göre, Kampaniyen-Maastrihtiyen [22], radyolarya ve planktik foraminifer içeriklerine göre [11,14] ise Senomaniyen-Maastrihtiyen (Geç Kretase) yaşı verilmiştir [15][16][17][18]. Birim için, güneye dalımlı okyanus içi ada yayı [23,24], aktif kıta kenarı [25] kuzeye dalımla gelişen ada yayı [26][27][28][29], ada yayı [30][31][32][33], okyanusal yay ortamları [34,35] ile okyanus içi yay-yay ardı sisteminde [11,12] oluştukları görüşleri kabul edilmiştir [14,36]. YK, Asker Dağı (Elazığ KD) civarında yaygın yastık lav morfolojili yüzlekler sunar [15][16][17].…”
Section: Sonuçlar Ve Tartışmalar (Results and Discussion)unclassified
“…Birim tabanda yer yer spilitk bazaltik yastık lavlar, bunlarla merceksel geometrili ve yer yer arakatıklı pelajik sedimanlar ile birlikte bulunmaktadır. Tabanda Guleman ofiyolitleri'ne ait serpantinleşmiş harzburjitler [34,35] ve gabroik kümülalar [47][48][49][50][51] görülmekle birlikte yer yer taban kayaları görülmeksizin doğrudan yer yer spilitik lavlarla başlayıp yer yer pelajik istiflerle arakatkılı yada ardalanmalı olarak bulunmaktadır. Birim, Hazar Grubu'nun gri renkli sedimanlarını uyumsuzlukla örtmektedir.…”
Section: Sonuçlar Ve Tartışmalar (Results and Discussion)unclassified
“…In addition, apart from the direct damage caused by the earthquake, a total of 30 landslides were triggered in an area of ~ 55 km2. In the study area, different types of rock units ranging in age from Paleozoic to Holocene are exposed (MTA, 2011;Kılınç and Ateş, 2015;Kılıç and Inceöz, 2015;Tekin et al, 2015;Ural et al, 2015Ural and Cihan, 2021;Rizeli et al, 2016Rizeli et al, , 2021Ertürk et. al, 2018Sar, 2016;Sar et al, 2019;Sar and Kürüm, 2022;Beyarslan et al, 2022) Many landslides were triggered from terrace edges cut into fluvial valley fill.…”
Section: Direct Effectsmentioning
confidence: 99%
“…The Guleman Ophiolite is thrusted over the Maden Complex, autochthon Arabian platform sediments and the Lice formation (Aktaş and Robertson 1984;Özkan andÖztunalı 1984, Kılıç 2009;Rizeli et al 2016;Uysal et al 2018). Sungurlu et al (1985) grouped the rocks in the Elazığ-Hazar-Palu region as autochthonous, allochtonous, paraallochtonous and neotochthonous units and concluded that most of these rocks are transported to the Arabian plate to the south.…”
Section: Geology and Stratigraphymentioning
confidence: 99%